Late diagnosed factor VII deficiency – a rare but significant haemorrhagic diathesis - Karolina Małgorzata Różycka; Beata Kuczyńska; Kinga Podsiadło; Małgorzata Mitura-Lesiuk; Irena Woźnica- Karczmarz (Pediatria Polska)
Factor VII (FVII) deficiency is a rare but significant inherited autosomal recessive coagulation disorder, occurring with a frequency of 1 in 300,000-500,000 people. The disorder is characterised by a wide range of bleeding symptoms that do not always correlate with plasma FVII levels, from asymptomatic conditions to severe haemorrhages. We present the case of a 2-year-old boy who was admitted to hospital for prolonged nosebleeds. Laboratory tests showed significant coagulation abnormalities: prolonged prothrombin time and international normalised ratio, directing suspicion to a rare coagulation disorder. Further diagnostics at a specialised centre confirmed congenital factor VII deficiency. The boy was observed to have repeated episodes of nosebleeds, and haematoma formation in the area of the knees, elbows, and fingers, even with minor trauma. Factor VII deficiency is a rare coagulation disorder, so each described case is important to better understand the clinical spectrum and therapeutic options.